Saturation mapping of consistent QTLs for yield and days to flowering under drought using locally adapted landrace in rice (Oryza sativa L.). (1st April 2019) - Rajurkar, Ashish B.; Muthukumar, C.; Bharathi, A.; Thomas, Helen Baby; Babu, R. Chandra
Highlights: Consistent QTLs linked to phenology, yield traits were detected using rice lines derived from a local landrace, Nootripathu under rainfed TPE. Consistent yield QTL on chromosome 1 was further refined to 42.8 Kb between RM11873-RM3825. Consistent DFF QTL on chromosome 6 was also refined to 279.8 Kb between RM19715-RM19727. Consistent QTLs for yield and DFF under drought showed linkage or pleiotropy to sd1 and Hd1 loci. Abstract: Drought stress is a major constraint for rice production in rainfed ecosystems. Landraces are reservoir of genes that can help in breeding drought tolerant cultivars. Utilizing the genetic potential of these locally adapted resilient germplasm using quantitative trait loci (QTL) mapping and marker-assisted breeding (MAB) will hasten development of high yielding drought resilient cultivars. A total of 60 genomic regions linked to phenology and plant production traits under drought predominant in rainfed target populations of environment (TPE) were mapped using rice lines derived from a locally adapted landrace, Nootripathu and drought susceptible elite cultivar, IR20 evaluated in three drought stress and one non-stress experiments in the field. QTLs important in rice adaptation to drought have been saturated and refined with additional markers. For example, consistent QTL, RM8085-RM3825 on chromosome 1 for grain yield under drought in TPE, with additive effect from the landrace has been narrowed down to 42.8 Kb (from 1.6 Mb) between RM11873-RM3825. Another QTL for yield under drought was also identified at RM11943 on chromosome 1 with additive effect from IR20 and is also linked to sd1 locus governing plant height. Similarly, the consistent QTL detected for days to 50% flowering (DFF), between RM314-RM6836 on chromosome 6 was also narrowed down to 279.8 Kb (from 4.9 Mb) between RM19715-RM19727. This QTL also harbours Hd1 locus regulating heading date. A QTL for yield under drought was also mapped on chromosome 6 near RM314. Both these QTLs for DFF and yield are located within the meta-QTL for yield under drought (MQTL6.1). These consistent QTLs for yield and DFF under drought in TPE with linkage or pleiotropy to sd1 and Hd1 loci mapped using rice lines derived from locally adapted landrace may be useful in MAB of rice cultivars suitable for water-limited environments.